2006
DOI: 10.1002/ijc.21891
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in risk of lung cancer: Expression of genes in the PAH bioactivation pathway in relation to smoking and bulky DNA adducts

Abstract: It is controversial whether women have a higher lung cancer susceptibility compared to men. We previously reported higher levels of smoking-related bulky DNA adducts in female lungs. In a pilot study (27 cases), we also found a higher level of female lung cytochrome P4501A1 (CYP1A1) gene expression. In the present extended study we report on the pulmonary expression of several genes involved in polycyclic aromatic hydrocarbon bioactivation in relation to sex, smoking and DNA adducts. CYP1A1, CYP1B1, aryl hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
92
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(103 citation statements)
references
References 22 publications
9
92
0
1
Order By: Relevance
“…6,15 We are showing here that DNA methylation of CYP1A1 enhancer inversely correlate with (i) the mRNA levels of CYP1A1 and (ii) levels of smoking-induced DNA adducts in histologically normal human lung tissues. Thus, in addition to the important role played by smoking-induced activation of the AHR/ARNT complex, inter-individual differences in CYP1A1 mRNA levels and in smoking-induced DNA damage may be due to inter-individual differences in DNA methylation of CYP1A1 enhancer.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…6,15 We are showing here that DNA methylation of CYP1A1 enhancer inversely correlate with (i) the mRNA levels of CYP1A1 and (ii) levels of smoking-induced DNA adducts in histologically normal human lung tissues. Thus, in addition to the important role played by smoking-induced activation of the AHR/ARNT complex, inter-individual differences in CYP1A1 mRNA levels and in smoking-induced DNA damage may be due to inter-individual differences in DNA methylation of CYP1A1 enhancer.…”
mentioning
confidence: 79%
“…15,37 Although methylation of the CYP1A1 enhancer region B was significantly higher in lung adenocarcinoma cell lines of male origin compared to female cell lines (data not shown), DNA methylation did not appear to be involved in sex differences in CYP1A1 gene expression in vivo. It should be noted that CYP1A1 gene expression can also be regulated by modifications of histone marks, and variations in AHR co-activators expression or activity.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…It should be noted that these findings were based on 109 cases and 423 controls, of which only 9 individuals carried the C/C genotype. While an early functional study suggested that CYP1A1 MspI variant genotypes result in increased ethoxyresorufin-O-deethylase (EROD) activity [21], later studies suggest that differing expression levels are due to polymorphisms in CYP1A1 exon 7 Ile 462 Val [22,23], and may also be influenced by smoking status [24] and gender [25,26].…”
Section: Cyp1a1 Mspimentioning
confidence: 99%
“…8 A link between cardiovascular disease and lung cancer in women, through oxidative stress has been supposed by a study run on a large cohort of patients with previous atherosclerotic disease-the female patients are more sensitive to tobacco-induced carcinogenesis than men, since a higher level of lung cytochrome P4501A1 (CYP1A1) gene expression in women plays a significant role in lung DNA adduct formation and supports a higher susceptibility to lung cancer among women. 35 Furthermore, we can suppose that the gender-different antioxidant status added to the less frequent women daily physical exercise, and/or the combination with other risk factors including ageing, smoking habit, obesity might share a co-aetiologic role in the diseases, such as cardiovascular diseases.…”
Section: D-roms Pat and Sat Tests And Gendermentioning
confidence: 99%